Numerical simulation of non-linear wave tank based on the ALE algorithm. (2013) - Zhu, Feng; Zhu, Weihua; Wang, Y.N.; Fang, B.; Zhao, S.L.
Numerical Wave Tank (NWT) becomes more and more prominent in the corresponding scientific research. On the basis of the Navier-Stokes (N-S) equation, the early application be adopted for discretising and calculating the specific region is by Volume of Fluid (VOF) and Finite Volume Method (FVM) method. But with the non-linear increasing size of calculation quantity, it becomes difficult to meet the requirements for engineering. However, ALE algorithm and SPH algorithm developed in recent years have the tendency to be mature enough to meet the engineering requirements. The calculation model of three-dimensional NWT is built by ALE algorithm as an example in this paper, and the results are compared with theoretical solution and experiment. The comparison has proved that ALE algorithm matches with the theoretical solution and experiment, and is suitable for engineering use.